2012
DOI: 10.2478/v10153-011-0086-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical activity with insulin resistance, subclinical inflammation, coagulation, and fibrinolytic biomarkers among population at high risk for type 2 diabetes

Abstract: Objective: To investigate the association of physical activity with insulin resistance and biomarkers of inflammation, coagulation, and fibrinolysis in a population at high risk for type 2 diabetes. Patients and Methods: A total of 778 subjects from the Risk factors in Impaired Glucose Tolerance for Atherosclerosis and Diabetes (RIAD) study aged 40-70 years were included in the present cross-sectional analysis. Results: Participants classified as having low physical activity (PA) were more insulin resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In the study of Stefano et al, it was observed that a significant inverse relationship between physical activity levels and insulin resistance exists, in line with previous reports, emphasizing the beneficial effects of exercise on insulin sensitivity in different populations (30). It has been shown that physical activity increases the insulin sensitivity through changes in body fat mass as well as through mechanisms independent of fat mass loss, such as: Increasing the transfer of GLUT4 and the subsequent use of glucose in skeletal muscle, improving the capacity of skeletal muscles for fat oxidation, increasing fat transfer of muscle cells, and reducing the amount of fat metabolites (30).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the study of Stefano et al, it was observed that a significant inverse relationship between physical activity levels and insulin resistance exists, in line with previous reports, emphasizing the beneficial effects of exercise on insulin sensitivity in different populations (30). It has been shown that physical activity increases the insulin sensitivity through changes in body fat mass as well as through mechanisms independent of fat mass loss, such as: Increasing the transfer of GLUT4 and the subsequent use of glucose in skeletal muscle, improving the capacity of skeletal muscles for fat oxidation, increasing fat transfer of muscle cells, and reducing the amount of fat metabolites (30).…”
Section: Discussionsupporting
confidence: 77%
“…It has been shown that physical activity increases the insulin sensitivity through changes in body fat mass as well as through mechanisms independent of fat mass loss, such as: Increasing the transfer of GLUT4 and the subsequent use of glucose in skeletal muscle, improving the capacity of skeletal muscles for fat oxidation, increasing fat transfer of muscle cells, and reducing the amount of fat metabolites (30).…”
Section: Discussionmentioning
confidence: 99%
“…Sedentary lifestyle is a pathogenic factor of obesity development and obesity-related cardiometabolic complications (8)(9)(10)(11)(12)(13)(14)(15). Increased physical activity and exercise training are well-established strategies for the treatment and prevention of obesity and its related diseases (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In Stefanov et al (2012) study, a significant inverse relationship was observed between physical activity and insulin resistance level which is in line with previous reports that emphasizes on beneficial effects of physical activity on insulin sensitivity in different populations (39). It has been shown that physical activity through changes in body fat mass and also mechanisms independent on fat mass, such as increased GLUT4 transport and consequently glucose uptake in skeletal muscle, improves the capacity of skeletal muscles for fat oxidation, increase muscle cells' fat transfer and reduces the amount of fat metabolites (39). In this regard, Jorge et al (2011) also observed no change in HOMA-IR index after 12 weeks of combined aerobic and resistance training (34).…”
Section: Discussionmentioning
confidence: 99%